Mind Mapping: Teaching Students to Think Critically on Basic Chemical Law Material - Aisyiyah Dinnur Utami; Eko Yuliyanto; Fitria Fatichatul Hidayah (Chemistry Education Department, 2021)
Chemistry materials with abstract and mathematical properties necessarily require the use of appropriate learning methods so that students can understand or relate concepts and explore their critical thinking skills. The aim of this study is to look at how mind mapping learning method has effects on students' critical thinking skills in basic chemical law material. It is a quasi-experimental study with a non-equivalent control group. Tests and questionnaires were used as research instruments. The variable measured was students' critical thinking. The findings reveal that mind mapping learning method has an effect on students' critical thinking skills. This can be seen from the average scores of student responses and better learning outcomes. There was an increase in critical thinking skills in the experimental class from the pre-test average score of 48.31 to the post-test average score of 51.40. Meanwhile, the control class went through a decrease from the pre-test average score of 47.95 to the post-test average score of 44.40. Students in the experimental class who were treated with mind mapping method performed better and had higher learning outcomes than students in the control class who did not receive the treatment.